EFEKTIVITAS WORKSHOP CANVA DALAM MENINGKATKAN KEMAMPUAN PRESENTASI AKADEMIK MAHASISWA - Andi Fidya Amalia; Waode Niscaya; Yesa Agustina; Ikhsan Ramadhan; Ishaq Faritsya; Zila Razilu (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Academic presentation skills are an important competency that college students must possess. However, many students are still unable to organize presentation media systematically, visually consistently, and in accordance with academic principles. This study aims to analyze the effectiveness of the Canva workshop implementation in improving the professional academic presentation skills of students at the University of Muhammadiyah Kendari. The study used a quantitative approach with a one-group pretest–posttest design. The research subjects were 40 students selected using a purposive sampling technique. Data were collected through presentation skills tests (pre-test and post-test) and analyzed using descriptive and inferential statistics in the form of paired t-tests. The results of the study showed an increase in the average score from 61.50 to 81.30. The t-test results showed a calculated t value of 30.60, which is greater than the t-table (2.02), so there is a significant difference between students' presentation skills before and after attending the Canva workshop. This study concludes that the Canva workshop is effective as a means of developing students' professional academic presentations. ABSTRAK Kemampuan presentasi akademik merupakan kompetensi penting yang harus dimiliki mahasiswa perguruan tinggi. Namun, masih banyak mahasiswa yang belum mampu menyusun media presentasi secara sistematis, visual konsisten, dan sesuai dengan kaidah akademik. Penelitian ini bertujuan untuk menganalisis efektivitas implementasi workshop Canva dalam meningkatkan kemampuan presentasi akademik profesional mahasiswa Universitas Muhammadiyah Kendari. Penelitian menggunakan pendekatan kuantitatif dengan desain one group pretest–posttest. Subjek penelitian berjumlah 40 mahasiswa yang dipilih menggunakan teknik purposive sampling. Data dikumpulkan melalui tes kemampuan presentasi (pre-test dan post-test) dan dianalisis menggunakan statistik deskriptif dan inferensial berupa uji t berpasangan. Hasil penelitian menunjukkan peningkatan nilai rata-rata dari 61,50 menjadi 81,30. Hasil uji t menunjukkan nilai t hitung sebesar 30,60 lebih besar dari t tabel (2,02), sehingga terdapat perbedaan yang signifikan antara kemampuan presentasi mahasiswa sebelum dan sesudah mengikuti workshop Canva. Penelitian ini menyimpulkan bahwa workshop Canva efektif sebagai sarana pengembangan presentasi akademik profesional mahasiswa.